Influence of Major Storm Events on the Quantity and Composition of Particulate Organic Matter and the Phytoplankton Community in a Subtropical Estuary, Texas - Reyna, Nicolas E.; Hardison, Amber K.; Liu, Zhanfei (Frontiers in Marine Science, 2017)
Variations in the freshwater inflow regimes of estuaries due to perturbations, such as storm events, alter the source and composition of particulate organic matter (POM) and the phytoplankton community, which are key links in estuarine carbon and nitrogen cycling. To evaluate the impact of varying freshwater discharge on POM quantity and composition and the phytoplankton community, monthly samples of surface water were collected at four long-term monitoring stations from 2012-2015 in a subtropical estuarine system, the Mission-Aransas Estuary, Texas (USA). This system is characterized by a semiarid climate, drought, and sporadic precipitation events. We analyzed organic carbon and nitrogen content, carbon and nitrogen stable isotopes, and chlorophyll a and accessory pigments of the POM samples. Following a prolonged dry spell (2012-2015), consecutive major storm events in spring 2015 led to a dramatic freshening of the entire estuary. Large increases in particulate organic carbon (POC) concentrations and decreases in δ13C values of POC over several weeks following the storms suggest an increase in in-situ production at lower salinities as a result of increased freshwater inflow. These changes in bulk POM coincided with an increase in chlorophyll a concentration, further indicating a significant contribution by phytoplankton to the elevated POM. Concurrently, pigment biomarkers revealed a significant (10-fold) increase in the cyanobacterial pigment, zeaxanthin, and further 16S rRNA analysis showed that Cyanobium spp. was responsible for the observed bloom. The combination of environment conditions, including freshening, high temperature, and high nutrients, likely contributed to the cyanobacteria bloom. These results show that episodic rain events can substantially affect estuarine phytoplankton community composition, which impacts the available energy resources for secondary production and thus may have ecosystem-wide implications on productivity.